Pengembangan LKPD Berbantuan Kvisoft Flipbook Maker pada Mata Pelajaran Teknologi Perkantoran di SMKN 2 Nganjuk - Elva Rohmatul Fitri; Triensninda Pahlevi (Jurnal Pendidikan Administrasi Perkantoran (JPAP), 2020)
The purpose of this study  was  to describe the process of developing LKPD and to find out the feasibility of LKPD which is assisted by Kvisoft Flipbook Maker in the X class OTKP office technology subjects at SMKN 2 Nganjuk . This study uses a  4D development model that is defining, designing, developing, and distributing. The assessment instruments used are material expert validation sheets, graphic expert validation sheets, and linguist validation sheets. This LKPD research development only reached the development stage because the purpose of this study was to produce products and test the feasibility of these products. At the development stage the researcher conducts this LKPD assessment to material, language and graphic expert validators.    The results of research on the feasibility of LKPD assisted by makers of Kvisoft Flipbooks show that the appropriateness of the content of the material obtained an assessment of 88.00% with the criteria of "very strong", the feasibility of the language obtaining an assessment of 87.14%, with the criteria of "very strong", and the eligibility of the graphic obtained an assessment of 87.06% with the criteria of "very strong" ". Recapitulation of all validation results, the LKPD assisted by Flipoft Maker Koftoft for office technology subjects in SMKN 2 Nganjuk received a worthiness of 87.40% with the criteria of "very strong" and said to be suitable for use in learning activities.